Urethral Prolapse Case Report: Surgical and Social Considerations in Senegal. (24th January 2022) - Jalloh, Mohamed; Heibig, Jennifer; Gaye, Oumar; Ghaul, William; Yankelevich, Gabrielle; Ndoye, Medina; Mbodji, Mouhamadou Moustapha; Cassell, Ayun; Niang, Lamine; Gueye, Serigne Magueye
Abstract : We present three cases of urethral prolapse in prepubertal females in Senegal who presented with vulvar bleeding. Careful gynecologic and urologic physical exams were performed and revealed urethral origin and prolapse. Conservative versus surgical approaches were taken in different patients, but ultimately, each patient received a urethral meatoplasty. Surgical excision of these masses yielded a full recovery in the patients. A careful review of the literature was then undertaken and showed that surgical excision or ligation of the prolapse is preferable to more conservative treatment. The case series article discusses the rare occurrence of urethral prolapse, as well as the epidemiology and prognostic and therapeutic implications of urethral prolapse in prepubertal females. Introduction . Urethral prolapse is a rare condition occurring mostly in young black females. It can be worrying to the parents as it often causes vulvar bleeding. Case Presentation . We present three cases of urethral prolapse in prepubertal females who presented with vulvar bleeding. Physical exams were performed and revealed urethral origin and prolapse. Each patient underwent a urethral meatoplasty and subsequently experienced a full recovery after respective follow-up of 2 years, 1 year, and 1 year. Conclusion . Urethral prolapse is a rare condition which can be managed successfully by surgery. Plain Language Summary . This case report on pediatric urethral prolapse showcases the different presentations and modalities of treatment, as the literature does not show that a specific treatment is always undertaken. In some countries, there are strong social considerations and they demonstrate difficulty separating sexual abuse from genitourinary pathologies, which are important to address in the treatment of these conditions.